Course finds PNG 'mecca' for probes - Mark Pearson (Asia Pacific Network, 2019)
Editors and news directors decided the controversial restructuring of operations at the University of Papua New Guinea was the story deserving deeper exploration. By the week's end, journalists had produced a series of feature and news stories for media exposés.